Basal insulin intensification with GLP-1RA and dual GIP and GLP-1RA in patients with uncontrolled type 2 diabetes mellitus: A rapid review of randomized controlled trials and meta-analysis - Lisco, Giuseppe; De Tullio, Anna; Disoteo, Olga; De Geronimo, Vincenzo; Piazzolla, Giuseppina; De Pergola, Giovanni; Giagulli, Vito Angelo; Jirillo, Emilio; Guastamacchia, Edoardo; Sabbà, Carlo; Triggiani, Vincenzo (Frontiers in Endocrinology, 2022)
Tirzepatide, a dual agonist of Glucose-Dependent Insulinotropic Polypeptide (GIP) and Glucagon-Like Peptide 1 (GLP-1) receptors, improved glucose control and reduced body weight in different therapeutic approaches. Herein, we overviewed the role of GIP and GLP-1 in the pathophysiology of type 2 diabetes and systematically reviewed the efficacy and safety of injectable incretin-based therapy added to basal insulin in light of the results of the SURPASS-5 trial. We identified eleven randomized clinical trials. GLP-1 receptor agonists (GLP-1RAs) or Tirzepatide added to basal insulin than rigorously titrated basal insulin significantly ameliorates glucose control (Δ HbA1c = -1%, 95% CI -1.25; -0.74, I2 94%; Δ FPG = -14.6 mg/dL, 95% CI -21.6-; -7.6, I2 90%; chance to achieve HbA1c <7% = RR 2.62, 95% CI 2.10; 3.26, I2 89%), reduces body weight (Δ = -3.95 kg, 95% CI -5.1, -2.79, I2 96%) without increasing the risk of hypoglycemia (RR = 1.01, 95% CI 0.86; 1.18, I2 7.7%). Tirzepatide provides an impressive weight loss exceeding that observed with GLP-1RAs. Injectable incretin-based therapy plus basal insulin remains a potent and safe therapeutic approach in uncontrolled type 2 diabetes patients previously treated with basal insulin alone. Tirzepatide is expected to ameliorate the management of “diabesity” in this usually difficult-to-treat cluster of patients.